Understanding Late Devonian and Permian-Triassic biotic and climatic events towards an integrated approach - Over, D. J.; Morrow, J. R.; Wignall, P. B. (Developments in palaeontology and stratigraphy ;, 2005)
The Late Devonian and Permian-Triassic intervals are among the most dynamic episodes of Earth history, marked by large secular changes in continental ecosystems, dramatic fluctuations in ocean oxygenation, major phases of biotic turnover, volcanism, bolide impact events, and rapid fluctuations in stable isotope systems and sea level. This volume highlights contributions from a broad range of geological sub-disciplines currently striving to understand these critical intervals of geologically rapid, global-scale changes. Provides updated, current models for the mid-Late Devonian and Permian-Triassic mass extinction episodes. Highlights several new analytical approaches for developing quantitative datasets. Takes an integrated approach presenting datasets from a broad range of sub-disciplines.